(untitled) (Papeles, 2015)
This text explores the concept simulation questioning some of its most widespread characterizations and argues why, contrary to these findings, all games are simulations. Subsequently, in order to specify what the particularity that differentiates the games from other forms of simulation is, Immersion category is proposed as one of the particular features of this medium. To explain this idea it is critically reviewed the work of some of the most prominent authors who have explored this concept, contrasting with different canonical definitions of play throughout the twentieth century and more recent reflections from the study of the game. Finally, the case of the video game “Atrapados” (Jaime Alejandro Rodríguez, 2014) is analized using the concepts of simulation and immersion to explain its functioning.